Mycophenolate-associated colitis in an orthotopic heart transplant patient- an unusual case presentation - Hajra Arshad, MD; Mohammad Yasrab, MD; Alejandra Blanco, MD; Jacqueline E Birkness-Gartman, MD; Elliot K. Fishman, MD (Radiology Case Reports)
Mycophenolate mofetil (MMF), an immunosuppressive, is a pharmacologically inactive compound of mycophenolic acid, which has been widely used in solid organ transplant and autoimmune conditions. It mostly exerts gastrointestinal (GI) adverse effects, which include diarrhea, abdominal pain, nausea, and vomiting. It can lead to MMF-colitis, a challenging condition to diagnose due to its similarity with other GI-related conditions and infections. This case report discusses a heart transplant recipient who developed severe MMF-induced colitis. It adds significantly to the limited literature available for this difficult-to-diagnose condition. It also highlights the severity of the condition and underscores the importance of vigilant monitoring and the need for future cohort studies to set guidelines for diagnosing and treating MMF-associated colitis due to its widespread use.